Acute respiratory failure among lung transplant adults requiring intensive care: Changing spectrum of causative organisms and impact of procalcitonin test in the diagnostic workup. Issue 5 (20th June 2020) - Tejada, Sofia; Campogiani, Laura; Mazo, Cristopher; Romero, Anabel; Peña, Yolanda; Pont, Teresa; Gómez, Aroa; Román, Antonio; Rello, Jordi
Abstract: Background: The aim was to identify the causing organisms and assess the association of procalcitonin (PCT) with bacterial pneumonia within 24 hours of intensive care unit admission (ICU‐A) among lung transplant (LT) adult recipients. Methods: Secondary analysis from a prospective cohort study. All LT adults admitted to ICU for acute respiratory failure (ARF) over 5 years were included. Patients were followed until hospital discharge or death. Results: Fifty‐eight consecutive LT patients were enrolled. The most important cause of ICU‐A due to ARF was pneumonia 29 (50%) followed by acute rejection 3 (5.2%) and bronchiolitis obliterans syndrome exacerbation 3 (5.2%). Microorganisms were isolated from 22/29 cases with pneumonia (75.9%): 17 (77.2%) bacterial, 4 (18.2%) viral, 1 (4.5%) Aspergillus fumigates, with Pseudomonas aeruginosa being the most common cause (45.5%) of pneumonia, with 10 patients presenting chronic colonization by P aeruginosa . Median [Interquartile range (IQR)] PCT levels within 24 hours after admission were higher in pneumonia (1.5 µg/L; IQR:0.3‐22.0), than in non‐pneumonia cases (0.2 µg/L; IQR:0.1‐0.7) ( P = .019) and PCT levels within 24 hours helped to discriminate bacterial pneumonia (8.2 µg/L; IQR:0.2‐43.0) from viral pneumonia and non‐pneumonia cases (0.2 µg/L; IQR:0.1‐0.7). The overall negative predictive value for bacterial pneumonia was 85.1%, increasing to 91.6% among episodes after 6 months of LT. Conclusions: Causes of severe pneumonia in LT are changing, with predominant role of P aeruginosa and respiratory viruses. PCT ≤ 0.5 μg/L within 24 hours helps to exclude bacterial pneumonia diagnosis in LT adults requiring ICU‐A. A negative PCT test allows antimicrobial de‐escalation and requires an alternative diagnostic to bacterial pneumonia.